2008
DOI: 10.1084/jem.20081588
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits Aβ production, neuritic plaque formation, and behavioral deficits in Alzheimer's disease mouse models

Abstract: Neuritic plaques in the brains are one of the pathological hallmarks of Alzheimer ' s disease (AD). Amyloid ␤ -protein (A ␤ ), the central component of neuritic plaques, is derived from ␤ -amyloid precursor protein (APP) after ␤ -and ␥ -secretase cleavage. The molecular mechanism underlying the pathogenesis of AD is not yet well defi ned, and there has been no effective treatment for AD. Valproic acid (VPA) is one of the most widely used anticonvulsant and mood-stabilizing agents for treating epilepsy and bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(170 citation statements)
references
References 45 publications
5
160
0
2
Order By: Relevance
“…VPA has been reported to reduce Aβ production (Qing et al, 2008b;Su et al, 2004) and attenuate neuronal loss in a murine transgenic model of Alzheimer's disease (Long et al, 2013). Our study showed that neither VPA nor PIA significantly altered the amounts of Aβ42 that bound to synapses.…”
Section: Discussionmentioning
confidence: 50%
“…VPA has been reported to reduce Aβ production (Qing et al, 2008b;Su et al, 2004) and attenuate neuronal loss in a murine transgenic model of Alzheimer's disease (Long et al, 2013). Our study showed that neither VPA nor PIA significantly altered the amounts of Aβ42 that bound to synapses.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, although VPA downregulated APP protein levels, transcriptional inhibition of APP mRNA was not affected in pancreatic (BxPC3) and colon adenocarcinoma (SW480) cell lines as demonstrated previously (70).…”
Section: ␤-Amyloid Precursor Protein Is a Tumor Growth Factormentioning
confidence: 57%
“…The mice trained to find the submerged platform in a 1.0-m-diameter pool of white, non-toxic colored water (temperature: 23°C). The procedure 34 consisted of 1 d of visible platform tests and 4 d of hidden platform tests, plus a probe trial 24 h after the last hidden platform test. In the visible platform test, mice were tested for 5 contiguous trials, with an intertrial interval of 30 min.…”
Section: Animalsmentioning
confidence: 99%